2016 International Symposium on Power Line Communications and Its Applications (ISPLC) 2016
DOI: 10.1109/isplc.2016.7476256
|View full text |Cite
|
Sign up to set email alerts
|

On the suitability of the Middleton class A noise model for narrowband PLC

Abstract: This paper analyzes the suitability of the Middleton canonical class A distribution to model the noise amplitude in narrowband power line communications (NB-PLC). The study has been accomplished using 311 noise registers measured in the CENELEC-A band.Obtained results indicate that this model has a quite limited capability to represent the measured noise, since only 14.47% of the registers have amplitudes drawn from this distribution. Nevertheless, the analysis of these successful cases provides practical info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…It is evident that when M is larger than 3, most of the parameters remain unchanged. Therefore, M is considered equal to 3, which is also proposed in [36]. From Figure 9, it can be noted that impulse index A in the noise measured in China is over 0.16, while it is lower than 0.04 in Figure 10.…”
Section: Middleton Class a Modelmentioning
confidence: 99%
“…It is evident that when M is larger than 3, most of the parameters remain unchanged. Therefore, M is considered equal to 3, which is also proposed in [36]. From Figure 9, it can be noted that impulse index A in the noise measured in China is over 0.16, while it is lower than 0.04 in Figure 10.…”
Section: Middleton Class a Modelmentioning
confidence: 99%
“…As classified in Fig. 4, discontinuous impulsive noise modeling typically includes the Gaussian Mixture [65], [115], [119], the Bernoulli Gaussian [104], [106], [108], Middleton's Classes [105], [116], [118] and the α-stable [113], [114] scenarios, which are introduced individually below.…”
Section: Simplified Mathematical Modelingmentioning
confidence: 99%
“…In previous studies [11,14], it has been shown that the Middleton Class A distribution can be simplified into a summation up to a finite scalar M, instead of performing the infinite summation in (1). In this study, we assume that M is 10, and the weight vector, P m in (1), is replaced with…”
Section: Middleton Class a Modelmentioning
confidence: 99%
“…In [10], Middleton Class A and α-Stable distributions are used to model impulsive noises in China and Italy, and it has been stated that PLC systems including high impulsive character can be modelled better with α-Stable distributions. Lastly, in [11], the suitability of Middleton Class A distribution has been evaluated under various conditions, and it has been shown that the Middleton Class A distribution has quite limited usage in PLC systems, due to failure in modelling the tail characteristics if the impulsive noise.…”
Section: Introductionmentioning
confidence: 99%